2007
DOI: 10.1055/s-2007-990236
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Effects of Carvacrol on the Blood Pressure of Normotensive Rats

Abstract: Carvacrol is the major compound of essential oils of many plants, ethnomedically used for centuries but there were no detailed investigations on its action on the cardiovascular system. The aim of our study was to investigate the role of carvacrol on the cardiovascular functions of anesthetized rats and in vitro of isolated rat aorta. Carvacrol (100 microg/kg, I. P.) decreased heart rate, mean arterial pressure and systolic and diastolic blood pressures of the anesthetized rats whereas there were no effects at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 20 publications
1
47
1
Order By: Relevance
“…In normotensive rats, carvacrol at a dose of 100 mg/kg (i.p.) reduced blood pressure and heart rate, and inhibited the hypertension induced by L-NAME (Aydin et al, 2007). However, in isolated rat aorta, although Aydin et al (2007) did not observe any significant effect of carvacrol, PeixotoNeves et al (2010) demonstrated that this monoterpene induced an endothelium-independent relaxation, possibly cholinergic/nitric oxide pathways (Johnson et al, 2009) and mediated by activation of transient receptor potential melastatin 8 (TRPM8) (Venkatachalam & Montell, 2007;Johnson et al, 2009).…”
Section: Carvacrolmentioning
confidence: 99%
See 1 more Smart Citation
“…In normotensive rats, carvacrol at a dose of 100 mg/kg (i.p.) reduced blood pressure and heart rate, and inhibited the hypertension induced by L-NAME (Aydin et al, 2007). However, in isolated rat aorta, although Aydin et al (2007) did not observe any significant effect of carvacrol, PeixotoNeves et al (2010) demonstrated that this monoterpene induced an endothelium-independent relaxation, possibly cholinergic/nitric oxide pathways (Johnson et al, 2009) and mediated by activation of transient receptor potential melastatin 8 (TRPM8) (Venkatachalam & Montell, 2007;Johnson et al, 2009).…”
Section: Carvacrolmentioning
confidence: 99%
“…Besides the activities described above, monoterpenes also produce significant effects on the cardiovascular system, promoting, among other actions, vasorelaxation, decreased heart rate, and hypotension (Peixoto-Neves et al, 2010;Bastos et al, 2010;Aydin et al, 2007;Magalhães et al, 2008). Thus, these monoterpenes can be useful as agents for prevention and/or treatment of cardiovascular diseases (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…T. schimperi contained important antifungal substances such as thymol, linalool, and carvacrol (Lakew, 2011). The pharmacological actions of the plant extracts were suggested to be parallel to their carvacrol contents (Aydin et al, 2007). Carvacrol is considered to be biocidal, resulting in bacterial membrane perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…(Inamuco et al, 2012;Luz Ida et al, 2012;Moschonas et al, 2012), Escherichia coli (Obaidat and Frank, 2009) and others (Nostro and Papalia, 2012). Furthermore, carvacrol has anticancer (Koparal and Zeytinoglu, 2003;, anti-hyperlipidemic (Aristatile et al, 2009), anti-inflammatory (Fachini-Queiroz et al, 2012Lima et al, 2012), anti-ulcer , antinociceptive (Cavalcante Melo et al, 2012;Guimaraes et al, 2010), antidepressant-like (Melo et al, 2011a), hypotensive (Aydin et al, 2007) and vasorelaxant activities (PeixotoNeves et al, 2010).…”
Section: Discussionmentioning
confidence: 99%